Estratégia e competitividade numa rede de hotéis: um estudo da rede Versare de hotéis - Moraes, Rodrigo do Nascimento (2008)
The huge web which involves new dimensions in the world communication and transportation areas, due to the globalization of the economies, has provided a growing improve of tourism in the last decades of the 20th century. Besides the tourism leveraging strategies, implemented by countries and regions, new business niches have risen, such as ecological, religious, business and third age tourism, which have leveraged the marketing flows. Due to these changes, being competitive is even more important in the company s everyday routines. Such scenario stimulates competitors to join forces in order to compete in even bigger scales. This dissertation presents, through a multicase study of companies associated to a hotel network, an analysis of the expectations of 16 hotel owners of the 20 hotels surveyed about their motivation to join the network and their satisfaction with the results after becoming part of the network. It was acknowledged that the companies associated to the network have a long way until they are fully developed, however, important factors for the success of these companies, such as trust and cooperation, had better results among all the surveyed aspects. And this is the joining force which unites the partners which will provide the improve of results, that are also relevant, as cost reduction and the hotels performance indexes. As the factor which got the lower results is the cost reduction, mainly in order to purchase equipment. Once the present work identifies the results in the network during a due time, it is suggested that measures in order to improve the obtained results should be taken as well a constant accompanying in order to foster the growth and the development of Rede Versare de Hotéis, besides new researches in the area.